Microarray Analysis of XOPS-mCFP Zebrafish Retina Identifies Genes Associated with Rod Photoreceptor Degeneration and Regeneration - Morris, Ann C. (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. XOPS-mCFP transgenic zebrafish experience a continual cycle of rod photoreceptor development and degeneration throughout life, making them a useful model for investigating the molecular determinants of rod photoreceptor regeneration. The purpose of this study was to compare the gene expression profiles of wild-type and XOPS-mCFP retinas and identify genes that may contribute to the regeneration of the rods. METHODS. Adult wild-type and XOPS-mCFP retinal mRNA was subjected to microarray analysis. Pathway analysis was used to identify biologically relevant processes that were significantly represented in the dataset. Expression changes were verified by RT-PCR. Selected genes were further examined during retinal development and in adult retinas by in situ hybridization and immunohistochemistry and in a transgenic fluorescent reporter line. RESULTS. More than 600 genes displayed significant expression changes in XOPS-mCFP retinas compared with expression in wild-type controls. Many of the downregulated genes were associated with phototransduction, whereas upregulated genes were associated with several biological functions, including cell cycle, DNA replication and repair, and cell development and death. RT-PCR analysis of a subset of these genes confirmed the microarray results. Three transcription factors (sox11b, insm1a, and c-myb), displaying increased expression in XOPS-mCFP retinas, were also expressed throughout retinal development and in the persistently neurogenic ciliary marginal zone. CONCLUSIONS. This study identified numerous gene expression changes in response to rod degeneration in zebrafish and further suggests a role for the transcriptional regulators sox11b, insm1a, and c-myb in both retinal development and rod photoreceptor regeneration.